Características bromatológicas de las conservas de tipo grated de sardina, expendidas en el mercado La Hermelinda – Trujillo, en el año 2012 - Cantos Huayla, Janeth Alejandra (2014)
The qualitative characteristics of canned sardine grated type, expended in the market The Hermelinda – Trujillo, at the year 2012 were determined. The brands were: ARACELLI, BRIALES, EL CHULLO, LA RICOTONA, PERUMAR, ROSALINDA, YANFISH, and TRADICION; to which underwent compositional analysis in three stages: physical appearance container, phycho-sensory content review, and chemical analysis. The results showed that 50% of the samples had a deficit in its net weight and drained, the cans had dents, swelling, rust, corrosion, mislabeled, and lot and expiration date were not printed in indelible ink. The psycho- sensorial analysis determined if the smell, color, taste and texture was the characteristic of the sardine. In 80% of samples regular amount of thorns, bones and scales were found. Qualitative chemical analysis showed that the 30, 75, and 40% of the samples was slightly positive reaction to Ebert, Amidosoda, and investigation of hydrogen sulfide, respectively. Determination of Volatile Basic Nitrogen and Sodium Chloride allowed to decide whether or not the samples were unfit for consumption. So we conclude that 82,5% of the samples were determined unfit for human consumption, while canned fish “LA RICOTONA” and “TRADICION” were not.